TBK1 is ubiquitinated by TRIM5α to assemble mitophagy machinery - Bhaskar Saha; Hallvard Olsvik; Geneva L. Williams; Seeun Oh; Gry Evjen; Eva Sjøttem; Michael A. Mandell (Cell Reports, 2024)
Summary: Ubiquitination of mitochondrial proteins provides a basis for the downstream recruitment of mitophagy machinery, yet whether ubiquitination of the machinery itself contributes to mitophagy is unknown. Here, we show that K63-linked polyubiquitination of the key mitophagy regulator TBK1 is essential for its mitophagy functions. This modification is catalyzed by the ubiquitin ligase TRIM5α and is required for TBK1 to interact with and activate a set of ubiquitin-binding autophagy adaptors including NDP52, p62/SQSTM1, and NBR1. Autophagy adaptors, along with TRIM27, enable TRIM5α to engage with TBK1 following mitochondrial damage. TRIM5α’s ubiquitin ligase activity is required for the accumulation of active TBK1 on damaged mitochondria in Parkin-dependent and Parkin-independent mitophagy pathways. Our data support a model in which TRIM5α provides a mitochondria-localized, ubiquitin-based, self-amplifying assembly platform for TBK1 and mitophagy adaptors that is ultimately necessary for the recruitment of the core autophagy machinery.